Emotional responding to overt and subtle social exclusion among young women who engage in non-suicidal self-injury - Robinson, Kealagh; Boyes, Mark; Wilson, M.S.; Grimshaw, G.M. (2023)
People who engage in non-suicidal self-injury (NSSI) consistently report greater emotion reactivity and dysregulation than their peers. However, evidence that these self-reports reflect an amplified emotional response under controlled conditions is limited. Here we test the effects of both subtle and overt social exclusion, to determine whether self-reported emotion dysregulation reflects responses to real-time emotional challenge for people who self-injure. We recruited 100 young women with past-year NSSI and 100 without NSSI to an online experiment. Participants took part in a baseline social inclusion ball-tossing game, followed by either an overt or subtle social exclusion ball-tossing game, while we measured negative mood and belongingness. Despite reporting greater emotion reactivity (d = 1.40) and dysregulation (d = 1.63) than controls, women with past-year NSSI showed no differences in negative mood or belongingness ratings in response to either overt or subtle social exclusion. Within the NSSI group, exploratory analyses found greater endorsement of intrapersonal functions predicted greater negative mood following social exclusion (β = 0.19). Given that amplified emotional responding is central to prominent theoretical models of NSSI, findings highlight the need to better understand the divergence in findings between self-reported emotion dysregulation and real-time emotional responding among people who self-injure.